Association between genetic variants of membrane transporters and the risk of high-grade hematologic adverse events in a cohort of Mexican children with B-cell acute lymphoblastic leukemia - Escalante-Bautista, Deyanira; Cerecedo, Doris; Jiménez-Hernández, Elva; González-Torres, Carolina; Gaytán-Cervantes, Javier; Núñez-Enríquez, Juan Carlos; Sepúlveda-Robles, Omar Alejandro; De Ita, Marlon; Jiménez-Morales, Silvia; Sánchez-López, José Manuel; Mata-Rocha, Minerva; Torres-Nava, José Refugio; et al. (Frontiers in Oncology, 2024)
Background: Advances in the understanding of the pathobiology of childhood B-cell acute lymphoblastic leukemia (B-ALL) have led towards risk-oriented treatment regimens and markedly improved survival rates. However, treatment-related toxicities remain a major cause of mortality in developing countries. One of the most common adverse effects of chemotherapy in B-ALL is the hematologic toxicity, which may be related to genetic variants in membrane transporters that are critical for drug absorption, distribution, and elimination. In this study we detected genetic variants present in a selected group genes of the ABC and SLC families that are associated with the risk of highgrade hematologic adverse events due to chemotherapy treatment in a group of Mexican children with B-ALL.Methods: Next generation sequencing (NGS) was used to screen six genes of the ABC and seven genes of the SLC transporter families, in a cohort of 96 children with B-ALL. The grade of hematologic toxicity was classified according to the National Cancer Institute's Common Terminology Criteria for Adverse Events (CTCAE) version 5.0, Subsequently, two groups of patients were formed: the null/lowgrade (grades 1 and 2) and the high-grade (grades 3 to 5) adverse events groups. To determine whether there is an association between the genetic variants and high-grade hematologic adverse events, logistic regression analyses were performed using co-dominant, dominant, recessive, overdominant and logadditive inheritance models. Odds ratio (OR) and 95% confidence intervals (95% CI) were calculated.We found two types of associations among the genetic variants identified as possible predictor factors of hematologic toxicity. One group of variants associated with high-grade toxicity risk: ABCC1 rs129081; ABCC4 rs227409; ABCC5 rs939338, rs1132776, rs3749442, rs4148575, rs4148579 and rs4148580; and another group of protective variants that includes ABCC1 rs212087 y rs212090; SLC22A6 rs4149170, rs4149171 and rs955434.There are genetic variants in the SLC and ABC transporter families present in Mexican children with B-ALL that can be considered as potential risk markers for hematologic toxicity secondary to chemotherapeutic treatment, as well as other protective variants that may be useful in addition to conventional risk stratification for therapeutic decision making in these highly vulnerable patients.